POWER SUPPLY APPARATUS, LIGHT EMITTING APPARATUS, AND DISPLAY APPARATUS - MIGUCHI, MITSUAKI (2006)
A power supply apparatus capable of effectively driving a plurality of load circuits. In a power supply apparatus (100), a booster circuit (10) supplies a drive voltage (Vout) to a plurality of light emitting diodes (300R-300B). A drive control part (20) controls the driving states, that is, light-emission intensities of the plurality of light emitting diodes (300R-300B). The drive control part (20) drives the plurality of load circuits in a time division manner, while the booster circuit (10) has an enable terminal and halts the switching operation during a non-light-emission period when none of the light emitting diodes (300R-300B) is driven by the drive control part (20). A light-emission pattern generator (32) generates light-emission control signals (SIG10R-SIG10B) that instruct the light emitting diodes (300) to emit lights. The booster circuit (10) performs a logic operation of these light-emission control signals (SIG10R-SIG10B), thereby halting the switching operation during the non-light-emission period when none of the light emitting diodes (300) emits any lights. Appareil d'alimentation pouvant piloter de façon efficace une pluralité de circuits de charge. Dans un appareil d'alimentation (100), un circuit élévateur (10) fournit une tension de pilotage (Vout) à une pluralité de diodes électroluminescentes (300R-300B). Une partie de commande de pilotage (20) commande les états de pilotage, autrement dit les intensités d'émission lumineuse de la pluralité de diodes électroluminescentes (300R-300B). La partie de commande de pilotage (20) pilote la pluralité de circuits de charge par division de temps alors que le circuit élévateur (10) possède une borne d'activation et interrompt la commutation pendant une période de non-émission de lumière, lorsque aucune des diodes électroluminescentes (300R-300B) n'est pilotée par la partie de commande de pilotage (20). Un générateur de motif d'émission de lumière (32) génère des signaux de commande d'émission de lumière (SIG10R-SIG10B) qui commandent aux diodes électroluminescentes (300) d'émettre de la lumière. Le circuit élévateur (10) effectue une opération logique sur ces signaux de commande d'émission de lumière (SIG10R-SIG10B), interrompant ainsi la commutation pendant la période de non-émission de lumière, lorsque aucune des diodes électroluminescentes (300) n'émet de lumière.